Amino acid-incorporated polymer network by thiol-ene polymerization - R. Yokose; T. Shimasaki; N. Teramoto; M. Shibata (eXPRESS Polymer Letters)
Triallyl L-alanine (A3A) and triallyl L-phenylalanine (A3F) were synthesized by reactions of L-alanine and L-phenylalanine with allyl bromide in the presence of sodium hydroxide, respectively. Thiol-ene thermal polymerization of A3A or A3F with pentaerythritol-based primary tetrathiol (pS4P) or pentaerythritol-based secondary tetrathiol (S4P) at allyl/SH 1/1 in the presence of 2,2'-azobis(isobutyronitrile) produced an amino acid-incorporated polymer network (A3ApS4P, A3A-S4P or A3F-S4P). Although the thermally cured resins were homogeneous and flat films, the corresponding thiol-ene photopolymerization did not give a successful result. Degree of swelling for each thermally cured film in N,Ndimethylformamide was much higher than that in water. The glass transition and 5% weight loss temperatures (Tg and T5) of A3F-pS4P and A3F-S4P were higher than those of A3A-pS4P and A3A-S4P, respectively. Also, A3F-pS4P and A3F-S4P exhibited much higher tensile strengths and moduli than A3A-pS4P and A3A-S4P did, respectively. Consequently, A3FpS4P displayed the highest Tg (38.7°C), T5 (282.0°C), tensile strength (9.5 MPa) and modulus (406 MPa) among all the thermally cured resins.